2012
DOI: 10.3109/09637486.2012.738650
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed as a functional food ingredient in bread-making

Abstract: The objective of this study was to determine the effects of grape seed (GS) on the rheological and bread-making properties, antioxidant activity and phenolic composition of bread. Wheat flour was replaced with GS at levels of 2.5%, 5.0% and 7.5%. GS increased the dough development time at a level of 5.0% but did not change it at levels of 2.5% and 7.5%. The dough stability value increased from 6.4 to 12.3 min with the increase of GS content from 0% to 7.5%. Mixing tolerance index decreased from 41.1 to 6.4 Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 28 publications
4
43
0
3
Order By: Relevance
“…[19] The bread antioxidant activity increased significantly with the increased dose of GSF substitution at the levels of 2.5, 5, and 7.5 g GSF/100 g WF. [20,21] GSF increased the dough development time at a level of 5.0%, but did not change it very much at the levels of 2.5 and 7.5%. When testing it at Farinograph, the dough stability (ST) value increased from 6.4 to 12.3 min with the increase of GSF content from 0 to 7.5%, mixing tolerance index decreased from 41.1 to 6.4 Brabender Units and dough extensibility value was higher in GSF added dough than in the control.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…[19] The bread antioxidant activity increased significantly with the increased dose of GSF substitution at the levels of 2.5, 5, and 7.5 g GSF/100 g WF. [20,21] GSF increased the dough development time at a level of 5.0%, but did not change it very much at the levels of 2.5 and 7.5%. When testing it at Farinograph, the dough stability (ST) value increased from 6.4 to 12.3 min with the increase of GSF content from 0 to 7.5%, mixing tolerance index decreased from 41.1 to 6.4 Brabender Units and dough extensibility value was higher in GSF added dough than in the control.…”
Section: Introductionmentioning
confidence: 76%
“…When testing it at Farinograph, the dough stability (ST) value increased from 6.4 to 12.3 min with the increase of GSF content from 0 to 7.5%, mixing tolerance index decreased from 41.1 to 6.4 Brabender Units and dough extensibility value was higher in GSF added dough than in the control. [20] Also, other studies revealed that the substitution of WF with GSF at the levels of 3, 5, and 7 g GSF/100 g WF has the effect of decreasing the falling number (FN) index, of increasing the alphaamylase activity in wheat-grape seed composite flour and of improving the dough rheological properties simultaneously with the increasing dose of the GSF substitution level. [22] GSF has been developed to add value to the crop and to improve the nutritional value of bakery products, [19] fact that will lead to a good balance of high antioxidant activity with consumer acceptability.…”
Section: Introductionmentioning
confidence: 99%
“…Various works have noted the modifications induced by these types of flours, such as the increase of α‐amylase activity, leading to a lower falling number (an indicator of enzymatic activity); and the possible interaction of seed lipids with gluten, starch, and hydrophobic components resulting in weaker consistency of the dough, increased viscosity, and delayed gelatinization of starch (Mironeasa and others , ). In contrast, Meral and Doǧan () described contrary results such as a strengthening activity of grape seed flours, ascribed to the covalent or noncovalent bonds between gluten proteins and phenols, obtaining stronger flours with higher extensibility and resistance.…”
Section: Functions In the Food Industrymentioning
confidence: 97%
“…TFM tayini Folin-Ciocalteu yöntemi kullanılarak belirlenmiştir (Meral and Doğan, 2013). Sonuçlar gallik asit eşdeğeri olarak ifade edilmiştir.…”
Section: Toplam Fenolik Madde Tayini (Tfm)unclassified
“…Örnekler üzerine metanolde günlük olarak hazırlanan % 0.004 konsantrasyondaki DPPH çözeltisinden 2 mL eklenmiş ve vorteks yardımıyla hızlıca karıştırılmıştır. Hazırlanan deney tüpleri karanlık bir ortamda 30 dk inkübe edilmiş ve spektrofotometrede (Shimadzu UVmini-1240 UV/VIS, Japan) 517 nm dalga boyunda kontrol örneğine karşı (2 mL metanol ve 2 mL DPPH çözeltisi içeren örnek) okuma yapılmıştır (Meral and Doğan, 2013 Nişasta süspansiyonunun, sıcaklık ve karıştırma etkisine maruz bırakılmasıyla, nişasta granülleri şişer ve nişasta süspansiyonu yüksek bir viskozite değerine ulaşır. Fakat şişen nişasta granüllerinin sürekli ısıtılması ve karıştırılmasıyla nişasta süspansiyonunda kırılmalar oluşarak viskozitede azalma meydana gelir.…”
Section: Dpph Radikali Temizleme öZelliğiunclassified